2008
DOI: 10.1007/s00432-008-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer

Abstract: The results of this study might suggest a minor association between polymorphism 5557G>A and a reduced risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…A longer OS was reported in the same study population for patients who are homozygous for the 60A allele (Okazaki et al, 2008). The ATM SNP determined in the current study (rs1801516, or G5557A) has recently been shown to have an association with a reduced risk of breast cancer (Schrauder et al, 2008). This particular SNP is not in linkage with the ATM SNPs T-77C and G60A (r 2 ¼ 0.22, based on HapMap data phase II, March 2008).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…A longer OS was reported in the same study population for patients who are homozygous for the 60A allele (Okazaki et al, 2008). The ATM SNP determined in the current study (rs1801516, or G5557A) has recently been shown to have an association with a reduced risk of breast cancer (Schrauder et al, 2008). This particular SNP is not in linkage with the ATM SNPs T-77C and G60A (r 2 ¼ 0.22, based on HapMap data phase II, March 2008).…”
Section: Discussionmentioning
confidence: 47%
“…However, theoretically the substitution of the negatively charged Asp to neutral Asn may influence the ATM's interaction with other proteins. This may be a likely explanation, because the Asp amino acid at position 1853 appears to be highly conserved trough evolution (Schrauder et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, African-American and Asian groups had lower allele frequencies: African-Americans 8.4 and 7.8% in cases and controls, respectively, and Asians, 2.3% in cases and 5.9% in controls. 23 Consistent with the frequency of polymorphism 5557G>A found in the Caucasian group by Bretsky and colleagues, 23 Schrauder and colleagues 17 reported, in German population, a frequency of 19.3% in the case group and of 25.3% in controls.…”
Section: Discussionmentioning
confidence: 59%
“…Schrauder and colleagues analyzed this variant by real time PCR, in 514 patients with BC and in 511 age-matched healthy controls, resulting in the association of this variant with the risk of developing BC (p = 0.04). 17 In European population, this variant has been described by Angéle and colleagues. 18 They found a higher frequency of homozygotes in cases of individuals with BC that received radiotherapy compared with those who did not (odds ratio [OR] 6.76), associating this variant with increased radio-sensitivity in breast tissue, and suggesting it as a risk factor that predisposes for reaction effects after radiotherapy.…”
Section: Studies Of Polymorphism 5557g>amentioning
confidence: 86%
“…Cases and controls were collected from 2002 to 2008 [26][27][28][29]. The BBCC is part of the Breast Cancer Association Consortium (BCAC) and has taken part in the validation of confirmed breast cancer susceptibility single nucleotide polymorphisms (SNPs) [30][31][32][33][34][35][36][37][38].…”
Section: Patient Cohortmentioning
confidence: 99%